Homozygous deep intronic variant in SNX14 cause autosomal recessive Spinocerebellar ataxia 20: a case report - Levchenko, Olga; Filatova, Alexandra; Mishina, Irina; Antonenko, Aleksey; Skoblov, Mikhail (Frontiers in Genetics, 2023)
Autosomal recessive spinocerebellar ataxia type 20, SCAR20 (MIM: 616354) is a rare syndromic form of hereditary ataxias. It characterized by the presence of progressive ataxia, intellectual developmental disorder, autism and dysmorphic features. The disease caused by biallelic variants in SNX14 gene that lead to loss of protein function. Typically, these variants result in the formation of a premature stop codon, a shift in the reading frame or a variant in canonical splicing sites, as well as gross rearrangements. Here we present the first case of a deep intronic variant c.462-589A>G in SNX14 identified in two sisters with SCAR20 from a consanguineous family. This variant resulted in the inclusion of a pseudo-exon 82 nucleotides long and the formation of a premature stop codon, leading to the production of a truncated protein (NP_722523.1:p.Asp155Valfs*8). Following an extensive diagnostic search, the diagnosis was confirmed using trio whole genome sequencing. This case contributes to expanding the spectrum of potential genetic variants associated with SCAR20.